(Acetonitrile-κN)pentacarbonyltungsten(0) - Christoph E. Strasser; Stephanie Cronje; Helgard G. Raubenheimer (Acta Crystallographica Section E, 2011)
The acetonitrile ligand in the title compound, [W(CH3CN)(CO)5], is coordinated end-on to a pentacarbonyltungsten(0) fragment with a W—N bond length of 2.186 (4) Å, completing an octahedral coordination environment around the W atom.